2013
DOI: 10.1371/journal.pone.0071109
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiectasis-Associated Hospitalizations in Germany, 2005–2011: A Population-Based Study of Disease Burden and Trends

Abstract: BackgroundRepresentative population-based data on the epidemiology of bronchiectasis in Europe are limited. The aim of the present study was to investigate the current burden and the trends of bronchiectasis-associated hospitalizations and associated conditions in Germany in order to inform focused patient care and to facilitate the allocation of healthcare resources.MethodsThe nationwide diagnosis-related groups hospital statistics for the years 2005–2011 were used in order to identify hospitalizations with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(73 citation statements)
references
References 25 publications
1
63
1
2
Order By: Relevance
“…A similar observation was reported in previous studies that bronchiectasis coexisted in 30%–57% of patients with COPD,4548 which significantly increased the duration of ICU stay and hospital admission46 as well as the mortality rate 4,48. On the other hand, a Germany study showed that, with bronchiectasis as the primary diagnosis, 39% of the hospitalized patients were found to be comorbid with COPD and emphysema 49. COPD and bronchiectasis share many features in common, presenting a similar inflammatory profile with symptoms of chronic cough and sputum production, and both sometimes overlap, complicating their discriminative diagnoses and treatments 50.…”
Section: Discussion Limitations and Conclusionsupporting
confidence: 83%
“…A similar observation was reported in previous studies that bronchiectasis coexisted in 30%–57% of patients with COPD,4548 which significantly increased the duration of ICU stay and hospital admission46 as well as the mortality rate 4,48. On the other hand, a Germany study showed that, with bronchiectasis as the primary diagnosis, 39% of the hospitalized patients were found to be comorbid with COPD and emphysema 49. COPD and bronchiectasis share many features in common, presenting a similar inflammatory profile with symptoms of chronic cough and sputum production, and both sometimes overlap, complicating their discriminative diagnoses and treatments 50.…”
Section: Discussion Limitations and Conclusionsupporting
confidence: 83%
“…COPD has a strong association with bronchiectasis in previous study [5]. Meanwhile, NTM is a potential risk factor for COPD [34].…”
Section: Discussionmentioning
confidence: 96%
“…Findings from Germany also show an increasing value of the standardized hospitalization rate due to bronchiectasis (from 1.6/100 000 inhabitants to 2.1/100 000 inhabitants) in the years 2006-2011. This rate was clearly higher in female than in male population (2.3/100 000 inhabitants vs. 1.4/100 000 inhabitants, respectively), and increased along with age, showing the highest value in women aged 65-74 years (7.4/100 000 inhabitants) [8].…”
Section: Discussionmentioning
confidence: 79%
“…The averaged value of the standardized mortality in Germany (study period 2006-2011) was 0.03/100 000 inhabitants, 80% of deaths due to bronchiectasis occurred in the case of people older than 65 years of age [8].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation